2023
DOI: 10.1108/k-03-2022-0415
|View full text |Cite
|
Sign up to set email alerts
|

Which is better? Business models of partial and cross ownership in an NEV supply chain

Abstract: PurposeTo examine how shareholding affects optimal profits, R&D innovation, NEV market scale and social welfare in two supply chain models with partial and cross ownership patterns.Design/methodology/approachThe gradual retreat of government subsidies has directly weakened the financial support available to the stakeholders of new energy vehicles (NEVs). In this context, upstream and downstream enterprises of NEV are constantly seeking new business models of cooperation to achieve possible win-wins. NEV su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 38 publications
0
1
0
Order By: Relevance
“…Sun et al studied the optimal technology R&D and advertising investment in the NEVs supply chain, considering the influence of government subsidies and advertising [16]. Zhu et al studied the impact of equity ownership on the R&D and innovation of NEVs, and found that battery suppliers would benefit from cross-shareholding in the supply chain, and cross-shareholding provided the greatest incentive for R&D of NEV batteries [17]. Liu et al studied the impact of different shareholding strategies on the vertical cooperative innovation of the NEVs supply chain, and found that vertical shareholding is conducive to improving the battery endurance, but battery suppliers are more inclined to choose crossshareholding strategies [18].…”
Section: The Nev Supply Chainmentioning
confidence: 99%
“…Sun et al studied the optimal technology R&D and advertising investment in the NEVs supply chain, considering the influence of government subsidies and advertising [16]. Zhu et al studied the impact of equity ownership on the R&D and innovation of NEVs, and found that battery suppliers would benefit from cross-shareholding in the supply chain, and cross-shareholding provided the greatest incentive for R&D of NEV batteries [17]. Liu et al studied the impact of different shareholding strategies on the vertical cooperative innovation of the NEVs supply chain, and found that vertical shareholding is conducive to improving the battery endurance, but battery suppliers are more inclined to choose crossshareholding strategies [18].…”
Section: The Nev Supply Chainmentioning
confidence: 99%